2022
DOI: 10.1002/slct.202103701
|View full text |Cite
|
Sign up to set email alerts
|

Lemon Juice: A Versatile Biocatalyst and Green Solvent in Organic Transformations

Abstract: Green chemistry is the basis for fast‐growing, eco‐friendly, alternative sustainable technologies for the development of chemical products without the use or generation of hazardous catalysts. The role of naturally occurring fruit juice as a catalyst or solvent in organic synthesis has gained focused interest across the globe. Lemon juice‐mediated synthesis has been widely explored recently as a highly significant, selective solvent and biocatalyst in organic synthesis. This review presents recent developments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Several interesting biotransformations of small molecules using different fruits and vegetables have reported in literature [ 7 10 ] but no such method is reported for the steroidal compounds. Steroidal compounds have large assortment in clinical applications with diversified functions—they are second biggest class of present-day drugs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several interesting biotransformations of small molecules using different fruits and vegetables have reported in literature [ 7 10 ] but no such method is reported for the steroidal compounds. Steroidal compounds have large assortment in clinical applications with diversified functions—they are second biggest class of present-day drugs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers across the globe are continually synthesizing compounds containing this prestigious scaffold to further explore its applications. [66] In this perspective, Thacker et al reported the synthesis and biological evaluation of coumarin-linked thiazoli-dinone derivatives 43 via a pyrazole linker as selective carbonic anhydrase inhibitors. [67] The synthesized compounds were assessed against cytosolic isoforms (hCA I and hCA II) and the trans-membrane tumor-associated isoforms (hCA IX and hCA XII).…”
Section: Thiazolidinone-coumarin Hybridsmentioning
confidence: 99%
“…Each component, comprising bark, leaves, berries, shells and seeds, harbors a wide array of phytoconstituents such as vitamins, proteins, pectin, starch, sugars, cellulose, polyphenols, flavonoids, lignin, ash, volatile oils, organic acids, and bases. Due to their acidic nature, aqueous fruit juices like those from lemon [25], pineapple [26], coconut [27], Acacia concinna [28], Piper longum [29] and Tamarindus indica [30] have been found to be a suitable replacement for various homogeneous acid catalysts. These diverse chemical constituents are not only beneficial but also serve as a source of inspiration across various scientific domains.…”
Section: Introductionmentioning
confidence: 99%